Consumers’ acceptance and willingness to pay for enriched foods: Evidence from a choice experiment in Italy - Concetta Nazzaro; Marcello Stanco; Anna Uliano; Giuseppe Marotta (Future Foods)
Over the last decades, consumer has evolved becoming increasingly responsible, showing a preference for those foods having a positive impact on health, society and environment. In particular, consumers are showing an increasing interest in food innovation and towards foods capable to produce health benefits, such as enriched foods, which can be considered as functional foods. As consumer acceptance is crucial to the success of food innovation, this study aims to investigate consumers’ acceptance for two innovative enriched foods: extra virgin olive oil enriched with longchain Omega-3 fatty acids (EPA and DHA), and a lutein-enriched durum wheat pasta. To achieve study's aim, a choice experiment has been realized, also to detect consumers’ WTP. The analysis involved 445 Italian consumers. Results show that price represents the attribute that most of all is able to affect consumers’ utility, followed by the presence of the functional element. Furthermore, the analysis also shows consumers’ WTP a price premium for the functional attribute, for both products considered in the study. Such results highlight useful insights for practitioners and outlines new perspectives for future research.